2012
DOI: 10.1007/s00190-012-0588-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-receiver single-channel multi-frequency GNSS integrity: outliers, slips, and ionospheric disturbances

Abstract: In this contribution the integrity of singlereceiver, single-channel, multi-frequency GNSS models is studied. The uniformly most powerful invariant test statistics for spikes and slips are derived and their detection capabilities are described by means of minimal detectable biases (MDBs). Analytical closed-form expressions of the phase-slip, code-outlier and ionospheric-disturbance MDBs are given, thus providing insight into the various factors that contribute to the detection capabilities of the various test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…The research has recently revealed the hardware delays to be temporally variable and different for each observation type (Collins et al 2010;Laurichesse et al 2009;Liu et al 2004;Odijk et al 2012;Teunissen and de Bakker 2013). When linear combination is applied, code and phase hardware delays are lumped together in b .…”
Section: Observation Equations Of the Single-frequency Pppmentioning
confidence: 99%
“…The research has recently revealed the hardware delays to be temporally variable and different for each observation type (Collins et al 2010;Laurichesse et al 2009;Liu et al 2004;Odijk et al 2012;Teunissen and de Bakker 2013). When linear combination is applied, code and phase hardware delays are lumped together in b .…”
Section: Observation Equations Of the Single-frequency Pppmentioning
confidence: 99%
“…In DIA, the detection process aims to decide by using a overall test whether some kind of bias or outlier is present; the identification process serves to decide in which channel of the measurement and/or process vector and at which epoch the bias/outlier occurred; in the adaptation process, the detected bias/outlier are corrected or discarded. The DIA methods have found widely applications in the geodetic community, e.g., to detect GNSS pseudorange outliers, phase cycle slips or ionospheric disturbances (Teunissen 1998;Teunissen and De Bakker 2013), station coordinate discontinuities (Perfetti 2006), etc. Also, by inversing the power function of the test, a concept called minimal detectable bias/outlier, some kind of reliability measure, can be derived which can be used to evaluate the strength of the measurement model (De Jong 2000;Koch 2015;Teunissen 1998), and hence further to conduct the design of the measurement model (Salzmann 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their different applications, all of the aforementioned arrays are, however, utilized for the purpose of the same functionality, that is, providing accurate corrections for the users. Ensuring the integrity and reliability of the corrections, even at the pre-analysis level, is therefore of great importance, see e.g., Teunissen (1998); Teunissen and de Bakker (2012).Integrity monitoring and quality control of the GNSS array model is the topic of this contribution. We confine our study to the single-epoch scenario as it is indeed the ultimate goal of the near real-time applications and, at the same time, brings us conservative thresholds of the reliability measures of the corresponding multi-epoch scenario.…”
mentioning
confidence: 99%